2018
DOI: 10.1111/1556-4029.13801
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Hard Tissue and Soft Tissue Dimensions of the Nose in Children: A 3D Cone Beam Computed Tomography Study

Abstract: This study using three-dimensional cone beam computed tomography (CBCT) images of children determined relationships between nasal skeletal and soft tissue measurements and assessed the association with sex, age, and skeletal maturation stage. Following reliability studies, skeletal and soft tissue parameters were measured on coded CBCTs of 73 children (28M:45F;6-13 yoa). Pearson and Mantel correlations were used to analyze associations between skeletal and soft tissues. Partial Mantel correlations were used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 33 publications
1
21
0
Order By: Relevance
“…Reconstruction of the nasal region is one of the most critical stages of the FR due to the complexity of this anatomical structure and subjectivity of the method. 9,13 Therefore, studies about the influence of different factors such as sex, age, and ethnicity on nose dimensions have been performed to provide data for a more reliable reconstruction. 1,9,18,19,27 Although some researchers suggested that the facial form and dimensions are not exclusively defined by the underlying skeletal tissues, the relationship between skeletal and soft tissue parameters could provide valuable information about the strength of correlation and accuracy of the prediction process.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Reconstruction of the nasal region is one of the most critical stages of the FR due to the complexity of this anatomical structure and subjectivity of the method. 9,13 Therefore, studies about the influence of different factors such as sex, age, and ethnicity on nose dimensions have been performed to provide data for a more reliable reconstruction. 1,9,18,19,27 Although some researchers suggested that the facial form and dimensions are not exclusively defined by the underlying skeletal tissues, the relationship between skeletal and soft tissue parameters could provide valuable information about the strength of correlation and accuracy of the prediction process.…”
Section: Discussionmentioning
confidence: 99%
“…4 Previous studies have suggested that the anthropomorphometric features of the face are influenced by several factors such as sex, ethnicity, age, and skeletal classes. 7,8,9,10 Thus, substantial knowledge about the biologic profile, craniofacial musculature, and skeletal anatomy is of great importance for human recognition through the FR technique, since the relationship between these factors contributes to the facial singularity of each individual. 1,3,11 Nasal morphology is an important feature for a reliable FR as the nose is the most central and prominent structure of the human face.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations